2013
DOI: 10.1002/hipo.22139
|View full text |Cite
|
Sign up to set email alerts
|

Long-term effects of neonatal hippocampal lesions on novelty preference in monkeys

Abstract: In a recent longitudinal study to assess the development of incidental recognition memory processes in monkeys, we showed that the effects of neonatal hippocampal lesions did alter incidental recognition memory only when the animals reached the juvenile period (Zeamer et al., 2010). The current follow-up study tested whether this incidental memory loss was long-lasting, i.e. present in adulthood, or only transitory, due to functional compensation with further brain maturation. The same animals with neonatal hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
32
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 20 publications
(32 citation statements)
references
References 56 publications
(81 reference statements)
0
32
0
Order By: Relevance
“…Details of the MRI-guided surgical procedures, lesion evaluation and rearing conditions were reported previously (Goursaud and Bachevalier, 2007; Zeamer et al, 2010). Development of cognitive functions was evaluated in the same cohorts of animals at different time points during development and included measures of object recognition memory (Heuer and Bachevalier, 2011a; Zeamer and Bachevalier, 2013; Zeamer et al, 2010), memory for location and object/place associations (Blue et al, 2013), memory for food/place associations (Glavis-Bloom et al, 2013) and working memory (Heuer and Bachevalier, 2011b, 2013). …”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Details of the MRI-guided surgical procedures, lesion evaluation and rearing conditions were reported previously (Goursaud and Bachevalier, 2007; Zeamer et al, 2010). Development of cognitive functions was evaluated in the same cohorts of animals at different time points during development and included measures of object recognition memory (Heuer and Bachevalier, 2011a; Zeamer and Bachevalier, 2013; Zeamer et al, 2010), memory for location and object/place associations (Blue et al, 2013), memory for food/place associations (Glavis-Bloom et al, 2013) and working memory (Heuer and Bachevalier, 2011b, 2013). …”
Section: Methodsmentioning
confidence: 99%
“…Pearson’s correlation analysis in the Neo-Hibo group was carried out to evaluate the relation between with the memory scores in recognition and working memory tasks (Heuer and Bachevalier, 2013; Zeamer and Bachevalier, 2013) and the DTI-derived measures with significant group difference revealed by TBSS analysis, volume-of-interest analysis, and tracts-defined analysis, as stated above. For the incidental object recognition task (Zeamer and Bachevalier, 2013), memory scores were represented by the percent looking at novel black-white pictures at delays of 120-s collected at 48 months of age ( n = 4).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Our previous studies have demonstrated that neonatal lesion of the hippocampus critically alter the development of memory processes, including visual recognition memory (Zeamer et al, 2010; Zeamer & Bachevalier, 2013), spatial memory (Blue et al, 2013; Glavis-Bloom et al, 2013), and working memory processes (Heuer & Bachevalier, 2011, 2013). These studies provide strong evidence that damage to the hippocampus has a deleterious and long-lasting effect on the development of memory as it does in adult subjects (Nemanic, et al, 2004; Alvarado & Bachevalier, 2005; Bachevalier & Nemanic, 2008).…”
Section: Introductionmentioning
confidence: 99%